Determination of Anti-inflammatory Properties of Asparagus officinalis Extract - Doaa M. Elnagar (Innovations in Biological Science Vol. 10, 2024)
Aim: The present work was designed to evaluate the anti-inflammatory properties of Asparagus officinalis (AO) extract on liver inflammation CGN-induced. Background: Inflammation itself results in more hepatic cell damage, and a flow of cytokines and chemokines called inflammatory mediators is released, which in turn leads to the accumulation of leukocytes, mast cells, and macrophages in the inflammation site. Materials and Methods: Forty male Swiss albino mice were divided randomly into four groups, 10/each. The first group acted as untreated control, the second group was treated daily with an oral dose of (500 mg/kg) AO extract for one week, the third group was treated with a single dose of 2%W/V carrageenan (CGN) intraperitoneally, and left for one week, the fourth group treated with carrageenan as a third group and AO extract as the second group. Results: CGN injection resulted in a significant increase of WBCs and platelets, elevation of liver enzymes, and proinflammatory cytokines (TNF- \(α\) and IL6). Morphological features of the tails showed severe necrosis, and histopathological examination of tail tissue displayed a heavy incidence of inflammatory cells in the dermis layer and liver revealing severe inflammation, steatosis, and ballooning. The present study showed that a single dose of carrageenan could induce severe hepatic inflammation represented by an increase in liver enzyme activities (ALT, AST, and ALP) which due to hepatocellular degeneration leads to the draining of enzymes in the bloodstream. Several studies declared that AO extracts improved the elevated liver enzymes by bisphenol A. Meanwhile, post-treatment with AO extract after CGN showed a significant decrease in WBCs, platelets, and physiological parameters. Histopathological analysis revealed less incidence of inflammation in the tail and liver tissue besides improvement of tissues and pathological score. Conclusion: Post-treatment with AO extract after CGN injection showed significant improvement manifested by lowering liver enzymes, cytokines, and liver inflammation.